Annals of Biomedical Engineering The Journal of the Biomedical Engineering Society - Duma, Stefan M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Annals of Biomedical Engineering is an interdisciplinary, international journal which presents original and review articles in the major fields of bioengineering and biomedical engineering. A major aim of bioengineering is to provide integrated approaches to the solutions of biological and biomedical problems. The philosophy is to provide engineering approaches to enhance the power of the scientific method, and to maintain a balance between experimental observation and quantitative analyses. While the development of theory and of mathematical models is strongly endorsed, these should be evaluated wherever possible using biological data from experiments that test specific hypotheses. .
Keywords: Medicine; Biochemistry; Mechanics; Biophysics; Biological physics; Biomedical engineering; Biomedicine, general; Biomedical Engineering and Bioengineering; Biological and Medical Physics, Biophysics; Classical Mechanics; Biochemistry, general